2017
DOI: 10.1016/j.jart.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and characterization of composite material based on epoxy resin and clay fillers

Abstract: The present work aims at investigating the effect of locally produced clay (Algeria), along with the effect of their size and rate on physical and mechanical properties of the composite material. This study is divided into two parts: The first one is devoted to the study of the composite material based on epoxy resin with kaolin, using different size fractions at rates ranging from 2% to 20%. The second part examines epoxy resin-based composite with calcined kaolin (metakaolin) with regard to the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Furthermore, Fröhlich et al [9] and Donnet [23] provided information on the characterization and reinforcement loading effect on polymer-based composite, which provided an understanding of the kind of filler loaded in rubber. Nanoclay particle sizes, irrespective of chemical and morphological properties, proved to have dominated effect on polymer composite where clay is used as reinforcement [10,28,29]. Laouchedi et al [28] investigated the effect of locally produced particle sizes and loading rate on epoxy composite material's physical and mechanical properties.…”
Section: Influence Of Particle Sizes and Loading Ratio Of Fillers On ...mentioning
confidence: 99%
“…Furthermore, Fröhlich et al [9] and Donnet [23] provided information on the characterization and reinforcement loading effect on polymer-based composite, which provided an understanding of the kind of filler loaded in rubber. Nanoclay particle sizes, irrespective of chemical and morphological properties, proved to have dominated effect on polymer composite where clay is used as reinforcement [10,28,29]. Laouchedi et al [28] investigated the effect of locally produced particle sizes and loading rate on epoxy composite material's physical and mechanical properties.…”
Section: Influence Of Particle Sizes and Loading Ratio Of Fillers On ...mentioning
confidence: 99%
“…[7] According Liu et al, [17] treated talc significantly improves the Charpy impact strength and tensile strength of polypropylene/talc composites. Some researchers [18,19] have found that the use of calcined kaolin improves the mechanical and thermal properties of some polymers. For example, calcined kaolin-loaded epoxy resins give better results compared to kaolinloaded ones.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy polymers give high strength, low shrinkage, good adhesion to various substrates, excellent electrical insulation, high chemical resistance, low toxicity and low cost. The three basic constituents of an epoxy system are: resin, curing agent and modifier [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%